Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 876 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Oreochromis mossambicus (Peters, 1852)", "Country is Mexico", "Geometry POLYGON((-165.76 -16.04,-165.76 47.34,-55.55 47.34,-55.55 -16.04,-165.76 -16.04))", "HasGeospatialIssue is false" ] } The dataset includes 876 records from 23 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000149-170627171947987/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences